2019
DOI: 10.2139/ssrn.3372135
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Public Procurement

Abstract: for their helpful comments. We are grateful to the Aalto Economic Institute for funding and negotiating the public procurement data, and to Cloudia Oy for sharing it and for providing their expertise. We thank the Yrjö Jahnsson Foundation for funding the Statistics Finland data. Jan Jääskeläinen also thanks Yrjö Jahnsson Foundation for the financial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
0
16
1
1
Order By: Relevance
“…According to Lucica Sintea, the procurement process must support genuine competition that facilitates the selection of the most effective offers, namely the purchase of the best product, service or work at the best price [5,48]. Usually, the participants in public procurement are different in size, which is likely to limit competition [6,2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lucica Sintea, the procurement process must support genuine competition that facilitates the selection of the most effective offers, namely the purchase of the best product, service or work at the best price [5,48]. Usually, the participants in public procurement are different in size, which is likely to limit competition [6,2].…”
Section: Resultsmentioning
confidence: 99%
“…Significant contribution to the development of the system of public procurement and its control and analytical support has been made by leading domestic scientists such as: L. Katrosha [1], G. I. Pinkas [2], V. Yu. Kwach [3], R. V. Afanasiev [3], A. V. Chernihivskaya [7], N. G. Zdyrko [14; 21], O. D. Shevchuk [14], J. V. Falko [15], and foreign experts: J. G. Murray (2009) [4], L. Sintea (2016) [5], J. Jääskeläinen & J. Tukiainen (2019) [6], D. Coviello (2017) [17], S. Gagliarducci (2017) [17], J. Palguta (2017) [18], F. Pertold, (2017) [18], M. Mironov (2016) [19], E. Zhuravskaya (2016) [19], K. Gugler (2015) [19], M. Weichselbaumer (2015) [20] and C. Zulehner (2015) [20].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Hal ini disebabkan karena masih terbatasnya akses data tender/seleksi pengadaan pemerintah ataupun belum diterapkannya sistem pengadaan secara elektronik. Sebagian besar negara maju yang memiliki data yang komprehensif dan tersedia bagi publik, telah menerapkan sistem eprocurement (Jääskeläinen & Tukiainen, 2019;İ. Onur, Özcan, & Taş, 2012Gupta, 2002.…”
Section: Latar Belakangunclassified
“…First, we speak to an emerging set of studies looking into competition in public procurement processes. Public procurement often suffers from an extremely low number of bids (e.g., Jääskeläinen and Tukiainen, 2019) and resulting high prices. 9 Hence, recent studies relate observed low levels of competition to procurement design and draw conclusions regarding procurers' tendency of raising entry barriers to improve supplier selection (Kang and Miller, 2020;Coviello et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we contribute to the literature on the spatial allocation of contracting firms and procurement authorities. Empirically, procurement contracts are often allocated to firms in the proximity of the contracting authority (Jääskeläinen and Tukiainen, 2019;Kutlina-Dimitrova and Lakatos, 2016). To some degree, this reflects natural entry costs, but both stated policy goals of "buy local" 10 and potential political connections (Szucs, 2018;Baltrunaite, 2019;Baltrunaite et al, 2020;Ryan, 2020;Baranek and Titl, 2020) have been used as explanations.…”
Section: Introductionmentioning
confidence: 99%